Bureaucracy, External Trade and Long-Term Growth in a Balance-of-Payments Constrained Growth Model (A Economia em Revista - AERE, 2018)
The debate surrounding the economic growth has been extended for a long time. This article follows the post-keynesian approach to the growth rate, introduced by Thirlwall (1979). The objective is to contribute to the debate surrounding the balance-of-payments constrained growth models, introducing the importance of bureaucracy in Moreno-Brid’s (2003) model. The developed model and the empirical analysis of the model that incorporates bureaucracy for a broader sample of countries for the period between 2008 and 2012 showed that the rate of growth of bureaucracy negatively and significantly affects the rate of output growth in the country, as expected, signaling that indeed the excess and positive variations of bureaucracy in a country relative to its trading partners, affect the competitiveness of their products and require more effort to attract external savings to finance the balance of payments, with all the consequences of this increased dependence on foreign capital, making the country relatively more vulnerable to problems in the domestic and international financial markets, which may culminate in a crisis in the balance of payments, with disastrous effects for long term economic growth.